A Review: Design Variables Optimization and Control Strategies of a Linear Switched Reluctance Actuator for High Precision Applications - Yeo Chin Kiat; Mariam Md Ghazaly; Shin Horng Chong; Irma Wani Jamaludin (International Journal of Power Electronics and Drive Systems (IJPEDS), 2017)
This paper presents the review of design variables optimization and control strategies of a Linear Switched Reluctance Actuator (LSRA).  The introduction of various type of linear electromagnetic actuators (LEA) are compared and the advantages of LSRA over other LEA are discussed together with the type of actuator configurations and topologies. The SRA provides an overall efficiency similar to induction actuator of the similar rating, subsequently the friction and windage losses are comparable but force density is better. LSRA has the advantage of low cost, simple construction and high reliability compare to the actuator with permanent magnet. However, LSRA also has some obvious defects which will influence the performance of the actuator such as ripples and acoustic noise which are caused by the highly nonlinear characteristics of the actuator. By researching the design variables of the actuator, the influences of those design variables are introduced and the detail comparisons are analyzed in this paper.  In addition, this paper also reviews on the control strategies in order to overcome the weaknesses of LSRA.